2017
DOI: 10.1501/commua1_0000000825
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solutions of the MRLW equation using moving least square collocation method

Abstract: Abstract. In this paper, the Modi…ed Regularized Long Wave (MRLW) equation is solved by using moving least square collocation (MLSC) method. To show the accuracy of the used method several numerical test examples are given. The motion of single solitary waves, the interaction of two solitary waves and the Maxwellian initial condition problems are chosen as test problems. For the single solitary wave motion whose analytical solution is known L 2 , L1 error norms are calculated. Also mass, energy and momentum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To carry out the spatial integration of Eq (6), we split the spatial domain into uniformly finite elements at the knots To construct the trigonometric quintic B-spline functions, we need 10 more knots outside the spatial domain as and . Then, trigonometric quintic B-splines at these knots are defined as other ise (7) where and…”
Section: Spatial Discretizationmentioning
confidence: 99%
See 3 more Smart Citations
“…To carry out the spatial integration of Eq (6), we split the spatial domain into uniformly finite elements at the knots To construct the trigonometric quintic B-spline functions, we need 10 more knots outside the spatial domain as and . Then, trigonometric quintic B-splines at these knots are defined as other ise (7) where and…”
Section: Spatial Discretizationmentioning
confidence: 99%
“…From Figure , it is observed that the solitary wave propagates to the right keeping its original shape. A comparison of the results obtained by the proposed algorithm with the some existing techniques given in [2,3,7,11,12,13,14,15] is provided in Table . Comparison verifies that the suggested algorithm gives much better results than the other techniques given in Table . The conservation invariants, the temporal rate of convergence and the error norm are given in Table 2. It can be noticed from Table that for the fixed space step, when the temporal step size is decreased from to , the temporal order of convergence is almost three and the calculated invariants are in almost good agreement with their theoretical values.…”
Section: The Motion Of the Single Solitary Wavementioning
confidence: 99%
See 2 more Smart Citations